2020
DOI: 10.1039/c9bm01636h
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic tissue models reveal the role of hyaluronan in melanoma proliferation and invasion

Abstract: Biomimetic matrix models demonstrate the role of the size-dependent effect of hyaluronan in melanoma progression and reveal an alternative explanation for in vivo findings of hyaluronan dependent melanoma growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 62 publications
5
19
0
Order By: Relevance
“…The current in vitro cell culture models, although far more simplified than the in vivo models in terms of biochemical and biophysical properties, decouple the necessary parameter of interest, namely tissue/fibril density. As our collagen matrices allow for additional modifications with other ECM components, for example fibronectin [26] and glycosaminoglycans [87,88], as well as a stepwise increase of matrix stiffness via crosslinker [23], we are capable of performing further studies on how matrix characteristics of higher complexities modulate macrophage phenotypes and functions. Additionally, further study will focus on spatio-temporal dynamics of cell-cell interactions during the tissue repair phase at a single cell resolution using label-free cell tracking [89].…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…The current in vitro cell culture models, although far more simplified than the in vivo models in terms of biochemical and biophysical properties, decouple the necessary parameter of interest, namely tissue/fibril density. As our collagen matrices allow for additional modifications with other ECM components, for example fibronectin [26] and glycosaminoglycans [87,88], as well as a stepwise increase of matrix stiffness via crosslinker [23], we are capable of performing further studies on how matrix characteristics of higher complexities modulate macrophage phenotypes and functions. Additionally, further study will focus on spatio-temporal dynamics of cell-cell interactions during the tissue repair phase at a single cell resolution using label-free cell tracking [89].…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Currently, less is known about matrix composition that might increase matrix stiffening. We previously reported that incorporation of fibronectin into 3D collagen matrices did not change matrix stiffness [11], while the presence of low-and high-molecular-weight HA enhanced the matrix elastic modulus [14,31]. Since activated fibroblastic cells might secrete a broad range of matrix proteins or crosslinking proteins (e.g., lysyl oxidase or transglutaminase) [51] that might contribute to increase of the matrix stiffening as well, we did not further characterize elastic modulus of decellularized matrix in dependence of HA depletion or other influences of composition or crosslinking.…”
Section: Tgf-β1 Enhanced Matrix Stiffening But Did Not Affect Proliferation and Asma Expression In Cafmentioning
confidence: 96%
“…One of the ECM components that has been discussed to be an important player in cancer progression is hyaluronan (HA) [13,14]. HA is a non-sulfated glycosaminoglycan composed of D-glucuronic and N-acetyl-D-glucosamine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantages of 2D tissue plastic cell culture are easier environmental control cell observation, measurement, and eventual manipulation in comparison with 3D cell culture models. As a major consequence non-physiological cell behavior and failure in the translation of cell culture results have been reported [126][127][128][129][130]. To better simulate the in vivo situation, more complex 3D models have been introduced for example using collagen, alginate, or PEG [38,[131][132][133][134].…”
Section: Technological Advances For Future Microgravity Researchmentioning
confidence: 99%